Healthy Planning: An Evolving Collaborative Partnership. Issue 1 (2nd January 2016) - Thompson, Susan; McCue, Peter
Abstract: Implementation of healthy planning initiatives is gathering pace across the globe as governments face escalating costs for chronic disease associated with sedentary lifestyles. Given that the built environment plays a critical role in supporting people being healthy as part of everyday life, the need to bring planning and health closer together is increasingly urgent. And while this need is largely uncontested, its activation is slow and difficult. In this paper we explore these issues using the evolving relationship between the disciplines of planning and health in New South Wales (NSW), Australia. Looking through the theoretical lens of "wicked problems" and the "applicability gap", we focus on telling the story of the strategic engagement of health in planning. This engagement led to the inclusion of two explicit health promotion objectives in the NSW State's draft planning legislation 2013. Our narrative begins at the broader Federal and state levels, which encompass a selection of key government, industry and NGO sector initiatives across the built environment and health disciplines. We then move to the specifics of our actions. The paper concludes with the challenges and opportunities of bringing health into planning that have applicability across different jurisdictions.